A systematic review of the challenges and solutions of ESL students' academic writing - Akhtar, R. (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
Research studies on ESL writing are more interested in providing operational writing strategies for academic writing. However, there are not many studies on challenges faced by students and their solutions. The main aim of this paper is to provide a systematic literature review of academic writing studies which focused on investigating students' academic writing challenges and their solutions. The papers used in this study were published from 2010 until 2019. A systematic search of literature proposed in this paper employs the exploratory approach for identifying and evaluating twenty-seven articles published in the authentic Journals. The themes of the review are divided into two categories, one which is related to ESL Malaysian students and another category is regarding non-Malaysians, this is due to the context of the study which will be conducted in Malaysia and therefore a review of studies done on Malaysian student academic writing is justified. The review shows there is a broader context of ESL students' academic writing challenges and factors influencing students' academic writing skills. In addition, as mentioned above, the review clearly shows the highlight of previous studies was on strategies which help improve students writing skills. As a conclusion, the review signifies that there are three major enormous challenges faced by ESL students in academic writing, such as teaching methods, students' attitude towards English, and language ability. And the solutions to the challenges are to employ active learning English language teaching methods, for example, Task-Based learning (TBL), Blended learning, Collaborative learning and cognitive approach, in teaching writing.